2020
DOI: 10.1111/are.14491
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary tryptophan levels and fish stocking density on immunological and antioxidant responses and bactericidal activity againstAeromonas hydrophilain rainbow trout (Oncorhynchus mykiss)

Abstract: Rainbow trout (Oncorhynchus mykiss) was reared under low (LD) and high (HD) stocking densities for 70 days, during which they were fed with diets supplemented with 0, 5 and 10 g tryptophan (Trp) per kg. At the end of the experiment, there were significant interaction effects of the stocking density and Trp levels on plasma Trp, globulin, lysozyme, catalase (CAT), malondialdehyde (MDA), and bactericidal activity and blood leucocyte count. However, there was no difference in plasma complement (ACH50), total immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…This enzyme breaks down the linkages of β‐1‐4 glycosidic bond present in the cell wall of bacteria that is between N‐acetylmuramic acid and N‐acetylglucosamine, thus inducing bacteriolysis to control the infection (Mukherjee et al, 2019). The increase in lysozyme in serum during the administration of immunostimulants indicates the increase in numerous humoral factors which protect the fish during pathogenic invasion (Hoseini et al, 2020; Hoseinifar et al, 2019). Our findings showed that the fish serum lysozyme activities were substantially increased in the subcellular injected group when compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme breaks down the linkages of β‐1‐4 glycosidic bond present in the cell wall of bacteria that is between N‐acetylmuramic acid and N‐acetylglucosamine, thus inducing bacteriolysis to control the infection (Mukherjee et al, 2019). The increase in lysozyme in serum during the administration of immunostimulants indicates the increase in numerous humoral factors which protect the fish during pathogenic invasion (Hoseini et al, 2020; Hoseinifar et al, 2019). Our findings showed that the fish serum lysozyme activities were substantially increased in the subcellular injected group when compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Stress physiology, markers of HSdensity stress and the effects of water quality, feed and water additive to reduce stress were reviewed by Baldwin (2011). Positive effects of feeding fish with some additives such as vitamins (Bacchetta et al, 2020;Naderi et al, 2017), fatty acids (Bahurmiz & Ng, 2007), amino acids such as arginine (Hoseini et al, 2019), tryptophan (Hoseini et al, 2020) and minerals (Adineh et al, 2020;Naderi et al, 2017) to reduce HSdensity stress have been found.…”
Section: Introductionmentioning
confidence: 99%
“…As the innate immune system in fish is vital in the response to primary stressors, as well as infectious diseases, the enhancement of innate immune responses, disease resistance, and subsequent improvement in health are of growing interest to researchers (Song et al, 2014;Yan et al, 2017;FAO, 2018). Immunostimulants present a promising approach to prevent and/or control diseases in aquaculture (Chakraborty and Hancz, 2011;Hoseinifar et al, 2015;FAO, 2018;Hoseini et al, 2019). Prebiotics have recently attracted extensive attention in aquaculture (Ringø et al, 2010), as non-digestible food ingredients that metabolizable through gut microbiota (Ringø et al, 2013).…”
mentioning
confidence: 99%